2020
DOI: 10.3892/ijmm.2020.4776
|View full text |Cite|
|
Sign up to set email alerts
|

Dendritic cell‑derived exosomal miR‑494‑3p promotes angiogenesis following myocardial infarction

Abstract: Infiltration by dendritic cells (dcs) is markedly increased in the infarcted area following myocardial infarction (MI), and dc ablation has been shown to impair angiogenesis in mice post-MI. Exosomes (EXs) have long been known to act as messengers between cells; however, whether EXs derived from dcs can enhance myocardial angiogenesis post-MI remains unknown. The aim of the present study was to elucidate whether EXs derived from dcs induce myocardial angiogenesis via paracrine signaling post-MI. In vitro, susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…Recently, it has been shown that the DCs infiltrating the infarcted myocardium following MI could induce angiogenesis by secreting the EXs containing highly expressed angiogenic miRs, particularly miR-494-3p. 52 It was found that miR-494-3-enriched MI-DC-EXs could be directly taken up by the cardiac microvascular endothelial cells (CMECs), significantly up-regulate the expression of the VEGF in CMECs, and thereby enhance angiogenesis in the infarcted myocardium after experimental MI. 52 In conclusion, MI-DC-EXs can promote recovery of the injured myocardium and improve cardiac function after MI through activating CD4 + Foxp3 + Tregs cells and inducing angiogenesis, providing a potent strategy for the treatment of MI.…”
Section: The Role Of Dendritic Cell-secreted Exosomes In Post-myocardial Infarctionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, it has been shown that the DCs infiltrating the infarcted myocardium following MI could induce angiogenesis by secreting the EXs containing highly expressed angiogenic miRs, particularly miR-494-3p. 52 It was found that miR-494-3-enriched MI-DC-EXs could be directly taken up by the cardiac microvascular endothelial cells (CMECs), significantly up-regulate the expression of the VEGF in CMECs, and thereby enhance angiogenesis in the infarcted myocardium after experimental MI. 52 In conclusion, MI-DC-EXs can promote recovery of the injured myocardium and improve cardiac function after MI through activating CD4 + Foxp3 + Tregs cells and inducing angiogenesis, providing a potent strategy for the treatment of MI.…”
Section: The Role Of Dendritic Cell-secreted Exosomes In Post-myocardial Infarctionmentioning
confidence: 99%
“…Besides, there is evidence showing the key role of DC‐EXs in angiogenesis following MI. 52 During the early phase after MI, angiogenesis plays an important role in the recovery of the injured myocardium and myocardial remodelling as well as maintenance of cardiac function 53 , 54 through healing the microvascular bed and preventing further necrosis and apoptosis of ischaemic myocardial tissue, which may be damaged, hibernating or stunned following MI. 53 Notably, DC ablation has been found to deteriorate angiogenesis and cardiac function in mice post‑MI, 12 supporting the determinant role of DCs in angiogenesis and cardiac healing after MI.…”
Section: Exosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, they were suggested as biomarkers for several diseases to set up diagnosis and disease progression. Their characteristics hold a great interest in designing therapeutic purposes in metabolic and genetic disorders, neurodegenerative and cardiovascular diseases, and cancer [12][13][14][15]. Nevertheless, different characterizations and validation methods have been developed whereby exosome purification and drug delivery are improved [1,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%